Aplicación del método didáctico “Layed” para desarrollar el aprendizaje holístico en los estudiantes del 1er grado de secundaria área CTA – CC.NN de la I.E N°00925 Santa Isabel – Nueva Cajamarca - Sopla Lazaro, Daza (2010)
The didactic method "LA YED" constitutes an interesting proposition to the traditional education, where we observe that the contents and educational methodology are linked to the educational process; in this case the Didactic Method LA YED allowed to improve education - learning process, managing to develop in the students a learning holistic. The main aim of this research was to apply the Didactic Method "LA YED" to develop the holistic learning with first grade students of secondary education, CTACCNN area. Of the I.E.00925 "Santa Isabel"- Neva Cajamarca. The Didactic Method "LA YED" has theoretical support in following : Discovery of Bruner's, significant learning, of Ausubel, genetic epistemologic, of Jean Piaget, In this way this theories helped to the Didactic method " LA YED" and was hipothetice the following : lf we apply the didactic method "LA YED" So lt will develop significantly holistic learning with first grade students of secondary education in the area of CT A - CCNN, of the lE N o 00925 - Neva Cajamarca The scheme of research was cuasi experimentally with pre test and post test; with two groups: experimental and control, these were intacts and no equivalent groups. The sample was shaped witch 68 students, 68 (G.C) and 34 (G.E). The Didactic Method "LA YED" was develop during the first quarter, reaching to validate our hypothesis of research, as statistical results shores where Z calculated (Zc =- 15, 14) is superior to the critica! value of Z tabulate (Zt = -1,64), being achieved to accept the hypothesis of investigation (Hi), it means that their average student's school performance the post test of the experimental group (X= 15.09) it (he, she) is superior to the average studenrs school performance the post test of the control group (X = 06,26); it is when we apply the Didactic Method "LA YED" improved significantly the student's learning holistic of first grade of secondary education in the area CTA- CCNN, of the lE N o 00925 "Santa Isabel"- Neva Cajamarca.